1999
DOI: 10.1111/j.1151-2916.1999.tb01966.x
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Way to Synthesize Yttrium Aluminum Garnet by Dissolving Yttria Powder in Alumina Sol

Abstract: A precursor for Y 3 Al 5 O 12 was synthesized as a YAG sol by simply dissolving Y 2 O 3 powder in an alumina sol. Phasepure Y 3 Al 5 O 12 powder was obtained by precipitating the YAG sol with an aqueous dilute ammonia solution followed by calcination at 1100°C. TG/DTA analysis showed an exotherm at 938°C attributed to formation of YAG phase and weight loss of 44% at 1000°C. XRD and FT-IR analysis showed that phase-pure YAG can be formed through noncrystalline and metastable hexagonal YAlO 3 without forming eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 9 publications
1
12
1
1
Order By: Relevance
“…It can be concluded that YAG appears to crystallize directly from the amorphous precursor without the formation of any intermediate phase, indicating the higher cation homogeneity of the precursor. This result differs from those of other wetchemical methods [14][15][16], in which yttrium aluminum perovskite (YAP) and yttrium aluminum monoclinic (YAM) usually appear as intermediate phases. At 1200°C, the diffraction peaks become stronger than peaks of sintered 1000°C.…”
Section: Resultscontrasting
confidence: 78%
“…It can be concluded that YAG appears to crystallize directly from the amorphous precursor without the formation of any intermediate phase, indicating the higher cation homogeneity of the precursor. This result differs from those of other wetchemical methods [14][15][16], in which yttrium aluminum perovskite (YAP) and yttrium aluminum monoclinic (YAM) usually appear as intermediate phases. At 1200°C, the diffraction peaks become stronger than peaks of sintered 1000°C.…”
Section: Resultscontrasting
confidence: 78%
“…2 shows the FT-IR spectrum of GdAlO 3 . The sample of GdAlO 3 exhibits the characteristic spectral pattern consisting of well-defined groups of sharp peaks in the range of 300 to 900 cm −1 , which is in agreement with the reported data [21]. The band observed in the low-frequency region of the spectrum, corresponds to the lattice vibration mode and may be attributed to gadolinium oxygen (Gd-O) vibration at 520 cm −1 .…”
Section: Infrared Spectrasupporting
confidence: 78%
“…The phase evolution shown by XRD indicates that YAG is the only phase detected during heat treatment. It can be concluded that YAG appears to crystallize directly from the amorphous precursor without the formation of any intermediate phase, such as YAP (YAlO 3 ) and YAM (Y 4 Al 2 O 9 ) that usually appear as intermediate phases in other wet-chemical powder preparation methods [9][10][11]. Fig.…”
Section: Resultsmentioning
confidence: 97%